Cage Environment Monitoring System in Modern Livestock: A Literature Review - Yohanes Adi Nugroho; Muhamad Fajar Imanul Haq; Reyhan Praditya Bagaskara; Diky Zakaria (Universitas Pendidikan Indonesia, 2024)
Livestock in Indonesia is one of the sectors that can have a considerableeconomic impact. However, livestock in Indonesia still implementsconventional livestock models so that livestock in Indonesia can still bedeveloped into modern livestock, one of the things that can improve theIndonesian livestock system is through a monitoring system or cagemonitoring. Therefore, the author conducted a literature review to find outhow the cage monitoring system on the livestock can work. Based on thestudy conducted by the author, the author can conclude that temperature,humidity, air quality, water quality and livestock movement are theparameters controlled by most researchers. These various parameters canbe monitored so that the system can control gas levels, temperature humidity. With this monitoring system, researchers believe that it canincrease the level of effectiveness in terms of cost and time so that it canalso indirectly increase the economic value of the livestock sector.